1979
DOI: 10.1099/00221287-115-1-167
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis Towards Sugars by Bacillus subtilis

Abstract: Many sugars and derivatives were tested in the capillary assay for their attraction of Bacillus subtilis. The major attractants were 2-deoxy-~-ghcose, D-fructose, gentiobiose, D-glucose, maltose, D-mannitol, D-mannose, N-acetylglucosamine, a-methyl-D-glucoside, P-methyl-Dglucoside, N-acetylmannosamine, a-methyl-D-mannoside, D-sorbitol, L-sorbose, sucrose, trehalose and D-XylOSe. Only glucose chemotaxis was completely constitutive. Competition experiments were carried out to determine the specificities of chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…To our knowledge prior to this study these two sugars were considered nonutilizable growth substrates by B. subtilis. However, previous studies showed gentiobiose and ␤-methyl-D-glucoside to be powerful attractants for B. subtilis chemotaxis (24,25), strongly suggesting that B. subtilis may indeed utilize these sugars. At present it is unknown whether gentiobiose and ␤-methyl-Dglucoside are transported and/or utilized by the bgl or lic gene products or if there exist specific genes coding for their transport and utilization.…”
Section: Resultsmentioning
confidence: 97%
“…To our knowledge prior to this study these two sugars were considered nonutilizable growth substrates by B. subtilis. However, previous studies showed gentiobiose and ␤-methyl-D-glucoside to be powerful attractants for B. subtilis chemotaxis (24,25), strongly suggesting that B. subtilis may indeed utilize these sugars. At present it is unknown whether gentiobiose and ␤-methyl-Dglucoside are transported and/or utilized by the bgl or lic gene products or if there exist specific genes coding for their transport and utilization.…”
Section: Resultsmentioning
confidence: 97%
“…This hypothesis is supported not only by the conserved localization of the MCPs (5,24,32,41,47) but also by the similar requirements among bacteria for sensitive sensory responses. Like E. coli, many types of bacteria, including B. subtilis (58,60) and S. aurantia (31), respond to changes in chemoeffector concentration over ranges spanning 4 to 6 orders of magnitude. This sensitivity suggests that they also require a means of signal amplification.…”
mentioning
confidence: 99%
“…It is not known whether 2-deoxyglucose is transported by a PTS system. Its chemotaxis is fourfold inducible rather than constitutive as is that of glucose, and thus 2-deoxyglucose probably is not just an analog of glucose (16). However, there are some interesting differences between taxis toward these sugars and taxis toward aspartate.…”
mentioning
confidence: 98%
“…Not just glucose but many sugars are transported by the PTS system (18), and many are also attractants for B. subtilis (16). However, the behavioral response to sugar addition is weak compared with amino acid addition.…”
mentioning
confidence: 99%